Digital Humanities and Libraries and Archives in Religious Studies An Introduction - Anderson, Clifford B. (Introductions to Digital Humanities - Religion, 2022)
How are digital humanists drawing on libraries and archives to advance research in the field of religious studies and theology? How can librarians and archivists make their collections accessible in return? This volume showcases the perspectives of faculty, librarians, archivists, and allied cultural heritage professionals who are drawing on primary and secondary sources in innovative ways to create digital humanities projects in the field.